Reader response as a focal practice in foreign language acquisition - Gonzalez, Ismel (My University, 2006)
This study describes the implementation of the reader response as a focal practice approach (Sumara, 1995) in a third year, Spanish as a foreign language class in a university setting, the nature of engagement and response experienced by the students, the ways that the reader response approach as a focal practice influences students’ oral language proficiency, comprehension, interpretation, and re-interpretation of a text and the implications this approach has in the foreign language curriculum at the university level. The design of the study was qualitative and emergent. Methods included participant and non-participant observation, taped responses, a taped focus group meeting, and analysis of documents. Six themes emerged from the data analysis: shifting roles in the foreign language classroom; patterns of shared response to La Casa en Mango Street; students’ attitudes towards a new pedagogical approach; students’ reading practices and priorities; response to La Casa en Mango Street, and pre- and post-unit language assessments. This study found that students’ oral proficiency, comprehension, interpretation and re-interpretation of the novel were positively affected by the reader response as a focal practice approach to foreign language literature. In addition, this approach allowed for social construction of meaning. The final culminating response to the novel allowed the participants to respond to it through a variety of symbol system such as drama, poetry, music and multi-media.
Keywords: Language and languages (Study and teaching); Language acquisition (Research); Language acquisition